2017
DOI: 10.1080/02109395.2016.1268388
|View full text |Cite
|
Sign up to set email alerts
|

Procedural differences in the calculation of the prevalence of reading difficulties in Spanish-speaking school children / Diferencias procedimentales en el cálculo de la prevalencia del retraso lector en escolares hispanoparlantes

Abstract: The prevalence of reading difficulties (RD) reflects controversial data ranging from 3.1–3.2% to 17.5%. Possible explanations are partly based on the incidence of orthography-specific factors influencing the reading process, but also on methodological differences that hinder comparison of the reported results. For this reason, the present study aims to analyse the prevalence of RD in a sample of 1,408 Spanish-speaking school children by comparing different ways of calculating the prevalence rate. The results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
1
1
0
2
Order By: Relevance
“…Interestingly, our calculation of the gender ratio regarding DD of boys to girls is about 2:1 (boys: 9.22%; 95% CI: 8.07–10.44%; girls: 4.66%; 95% CI: 3.84–5.54%) ( p < 0.001). This result is consistent with previous studies that reported a higher prevalence of DD for boys than for girls [ 31 , 35 , 51 ]. One explanation for this gender difference in DD prevalence is that some teachers are more likely to refer boys for assessment as having special problems because boys are often perceived as being more disruptive than girls [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, our calculation of the gender ratio regarding DD of boys to girls is about 2:1 (boys: 9.22%; 95% CI: 8.07–10.44%; girls: 4.66%; 95% CI: 3.84–5.54%) ( p < 0.001). This result is consistent with previous studies that reported a higher prevalence of DD for boys than for girls [ 31 , 35 , 51 ]. One explanation for this gender difference in DD prevalence is that some teachers are more likely to refer boys for assessment as having special problems because boys are often perceived as being more disruptive than girls [ 52 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the gender ratio of DD is the subject of an ongoing debate [ 31 , 32 , 33 ]. Most studies reported that more boys suffered from DD than girls, and the gender ratio of boys to girls was about 3:1 [ 34 , 35 , 36 ], but some studies found no differences in the prevalence of DD between boys and girls [ 18 , 31 ]. The latter interpreted the over-representation of boys in DD prevalence to be a result of bias in behavioral observation [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…En Uruguay (Montevideo), en 2011, Cuadro et al (2017), para 1.408 estudiantes de segundo a sexto de Educación Primaria, indican una prevalencia del 2,2-5,3%. En 2018, también en Montevideo, Costa-Ball (2021), para una muestra de 1.820 estudiantes de segundo a sexto, encuentra una prevalencia del 4,88%.…”
Section: Decisiones Académicas Del Alumnado Con Dislexia Del Desarrollounclassified
“…Participan grupos de investigadores provenientes de distintas disciplinas, con la activa participación de estudiantes de grado, maestrías y doctorados, y de trabajo en redes con grupos de investigación internacionales. Estudios publicados recientemente dan prueba de estos avances; por ejemplo, en el campo de la cognición numérica 31 o en el área del lenguaje escrito con trabajos sobre prosodia y competencia lectora 35 , alfabetización inicial, prevalencia del déficit lector 36 o procesos implicados en la adquisición de las representaciones ortográficas 37 .…”
Section: Experiencias Y Perspectivasunclassified